TED Talks Effect on Tenth Grade Students’ Vocabulary Mastery at SMAS GKPI Padang Bulan - Zebua, Vilmin Artinia; Tampubolon , Sahlan; Sinaga, Nenni Triana; Wafa, Ali (English Education Department, Faculty of Teacher Training and Education, Islamic University of Jember, 2025)
The TED Talks Application is an application that features talks on Technology, Education, Design, and various other topics, delivered by experts and professionals from around the world. This study aims to determine whether the TED Talks Application affects students’ vocabulary mastery. This research used an experimental quantitative method involving two classes of tenth-grade students at SMAS GKPI Padang Bulan, Indonesia. Using a purposive sampling technique, the sample consisted of 26 students in the experimental group and 26 students in the control group. Both groups received pre-tests and post-tests to measure vocabulary improvement. The average pre-test score in the experimental group was 40.76, while the post-test average was 57.76. The control group’s pre-test average was 40.38, and the post-test average was 50. Statistical analysis showed Ha was accepted and Ho was rejected, with a t-count of 2.677 greater than the t-table of 2.010. These results indicate that the TED Talks Application has a positive effect on students’ vocabulary mastery, although the effect size was relatively small. The findings suggest that while TED Talks are not ideal as the primary vocabulary tool, they remain useful as a supplementary resource. Further research is recommended to explore additional multimedia tools that may better enhance vocabulary learning outcomes.